(untitled) (Лучшие интеллектуальные исследования, 2025)
This article examines the effectiveness of the Lexical Approach in promoting long-term vocabulary retention among learners of English as a Second Language (ESL). Based on the idea that language is acquired in chunks rather than single words, the Lexical Approach has gained popularity as a method to improve communicative fluency and vocabulary depth. This paper explores the theoretical foundations of the approach, outlines practical classroom applications, evaluates research findings, and highlights challenges in its implementation. It concludes that while not having any limitations, the Lexical Approach significantly enhances vocabulary retention when properly integrated into classroom instruction.